A new species of Downeshelea Wirth & Grogan and a redescription of the male of Downeshelea cebacoi (Lane & Wirth) (Diptera: Ceratopogonidae) - Felippe-Bauer, Maria Luiza; Da Silva, Tiago Do Nascimento; Ribeiro, Enaly Silva; Borkent, Art (Zootaxa, 2011)
A new species of predaceous midge, Downeshelea lanei Felippe-Bauer & Borkent, is described and illustrated based on male and female specimens from the Amazonian Region of Brazil. The male of Downeshelea cebacoi (Lane & Wirth) is redescribed and illustrated and the distribution of this species is now restricted to Panama and Costa Rica.